Perlindungan Hukum Konsumen dalam Layanan Asuransi Digital: Tinjauan Yuridis Atas Tantangan Regulasi di Indonesia - Noor, Tajuddin; Zulkifli, Suhaila (Wajah Hukum, 2025)
This study aims to examine the form, characteristics, and regulatory challenges of digital technology-based insurance services (Insur Tech) in Indonesia, as well as to evaluate the form of legal protection available to policyholders in the context of the digital economy. The method used is a normative legal approach with an analysis of regulations such as POJK No. 36/2024 and POJK No. 8/2024, as well as literature and secondary sources from scientific articles and credible references. The research findings indicate that the development of InsurTech has not been matched by an adequate regulatory system, leading to potential legal uncertainty and weak consumer protection. The gap between technological innovation and regulatory response is evident in the lack of legal clarity regarding data security, service transparency, and dispute resolution mechanisms. The conclusions of this study emphasize the importance of regulatory updates that can ensure a balance between digital innovation and legal protection, through a collaborative approach between regulators, industry players, and the public. This research contributes to the development of digital law in the financial sector, particularly in shaping a legal framework that is more responsive to digital transformation in the insurance industry.